1988
DOI: 10.1111/j.1939-0025.1988.tb01600.x
|View full text |Cite
|
Sign up to set email alerts
|

A group for parents of children with fatal genetic illnesses.

Abstract: Parents whose children have progressive genetic disorders, such as Tay-Sachs, are confronted with a myriad of painful and compelling issues. This paper describes a long-term, open-ended group set up to allow parents of such children to work together on mutual concerns. The process of collaboration, the evolving structure of the group, and the challenges of working with this special population are explored.ith a growing awareness of the emo-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Chapters of the National Thy-Sachs and Allied Disease Association (NTSAD) have founded groups for families of children with Tay-Sachs disease and other fatal illnesses (Mack & Berman, 1988). The organization is unique in its collaboration with genetic professionals and professionals fkom other groups as well as in its ability to work with families of children both during their child's illness and after their death.…”
Section: Resourcesmentioning
confidence: 99%
“…Chapters of the National Thy-Sachs and Allied Disease Association (NTSAD) have founded groups for families of children with Tay-Sachs disease and other fatal illnesses (Mack & Berman, 1988). The organization is unique in its collaboration with genetic professionals and professionals fkom other groups as well as in its ability to work with families of children both during their child's illness and after their death.…”
Section: Resourcesmentioning
confidence: 99%
“…The families, who feel abandoned after their child dies, receive an "ongoing sense of security and support" from the group. 1 A child's progressive disease can have an impact on the school community, as described in the case report of a 7-yearold boy with adrenal leukodystrophy. 3 The boy's terminal status was acknowledged with a DNR request, but despite his tenuous condition, the boy and his parents wanted him to continue in school as long as possible.…”
Section: Issues Facing Caregivers and The Communitymentioning
confidence: 99%
“…1 The parents of children with Tay-Sachs in this descriptive article could not rely on a family network because they often found themselves ostracized from their closest relatives, who were unable to accept the family affliction and its genetic origins.…”
Section: End-of-life Issues In Genetics: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoak and Chesler (1985) similarly found that 52% of the groups they studied were led either by a professional or co-led by a professional and a nonprofessional self-helper. In addition to articles such as these, much of the available literature on selfhelp is devoted to research that involved professionals and self-help groups (e.g., Mack & Berman, 1988;Silverman, 1976;Storer, Frate, Johnson, & Greenberg, 1987) and to publications that described ways in which professionals may assist self-help groups (e.g., Gartner & Riessman, 1982;Gitterman, 1989;Powell, 1987Powell, , 1990van der Avort & van Harderden, 1985).…”
Section: Relationships Between Professionals and Self-helpersmentioning
confidence: 99%